Unveiling Mysteries in Congenital Diseases: A Case Report of Williams-Beuren Syndrome - Zixi Zhang; Cancan Wang; Qiuzhen Lin; Yichao Xiao; Qiming Liu (Cardiovascular Innovations and Applications)
Williams-Beuren syndrome (WBS) is an autosomal dominant genetic disorder closely associated with cardiovascular malformations, distinctive facial features, impaired cognitive ability, abnormal growth and development, endocrine dysfunction, and other related systems. In patients with WBS, the presence of cardiovascular malformations often necessitates genetic testing. This testing not only confirms the diagnosis but also facilitates the identification of associated syndromic features. Early and accurate diagnosis through genetic testing is instrumental for guiding further investigations, and initiating targeted therapies and support services. Such proactive management can substantially improve prognosis and quality of life for patients with WBS. Although surgery remains the most effective approach for repairing cardiovascular malformations, its implementation entails notable surgical risks. Clinicians should prioritize the identification and diagnosis of WBS, and strive to develop an effective management model involving collaboration among hospitals, families, and society. Here, we presented a case report of a patient with WBS and congenital heart disease, to contribute to a deeper understanding of this condition.